Photoexcited Carrier Transfer in CuInS2 Nanocrystal Assembly by Suppressing Resonant‐Energy Transfer - Hamanaka, Yasushi; Okuyama, Satoshi; Yokoi, Rin; Kuzuya, Toshihiro; Takeda, Keiki; Sekine, Chihiro (ChemPhysChem, 2023)
High‐density assemblies or superlattice structures composed of colloidal semiconductor nanocrystals have attracted attention as key materials for next‐generation photoelectric conversion devices such as quantum‐dot solar cells. In these nanocrystal solids, unique transport and optical phenomena occur due to quantum coupling of localized energy states, charge‐carrier hopping, and electromagnetic interactions among closely arranged nanocrystals. In particular, the photoexcited carrier dynamics in nanocrystal solids is important because it significantly affects various device parameters. In this study, we report the photoexcited carrier dynamics in a solid film of CuInS2 nanocrystals, which is one of the potential nontoxic substitutes with Cd‐ and Pb‐free compositions. Meanwhile, these subjects have been extensively studied in nanocrystal solids formed by CdSe and PbS systems. A carrier‐hopping mechanism was confirmed using temperature‐dependent photoluminescence spectroscopy, which yielded a typical value of the photoexcited carrier‐transfer rate of (2.2±0.6)×107 s−1 by suppressing the influence of the excitation‐energy transfer. Photoexcited carrier transfer in high‐density assemblies of Cd‐ and Pb‐free semiconductor nanocrystals of chalcopyrite CuInS2 is investigated. By suppressing the competing process via excitation‐energy transfer between nanocrystals, thermally activated scheme of excited carrier transfer is observed, and their characteristic parameters are determined.